Binder-Free Immobilization of Photocatalyst on Membrane Surface for Efficient Photocatalytic H2O2 Production and Water Decontamination - Zhen-Yu Hu; Tian Liu; Yu-Ru Yang; Alicia Kyoungjin An; Kim Meow Liew; Wen-Wei Li (Nano-Micro Letters)
Highlights Polyvinylidene fluoride nanofibers were treated by dimethylformamide to create micropores on membrane surface. Photocatalysts were firmly bounded by nanofibers during stretching and shrinking. Particulate catalysts were fixed yet high exposed on the membrane surface. Surface self-bounded photocatalytic membrane exhibited tenfold higher decontamination activity than embedded catalyst.